PD trafficking of potato leaf roll virus movement protein in Arabidopsis depends on site-specific protein phosphorylation - Link, Katrin; Vogel, Florian; Sonnewald, Uwe (Frontiers in Plant Science, 2011)
Many plant viruses encode for specialized movement proteins (MP) to facilitate passage of viral material to and through plasmodesmata (PD). To analyze intracellular trafficking of potato leaf roll virus (PLRV) movement protein (MP17) we performed GFP fusion experiments with distinct deletion variants of MP17. These studies revealed that the C-terminus of MP17 is essential but not sufficient for PD targeting. Interestingly, fusion of GFP to three C-terminal MP17 deletion variants resulted in the accumulation of GFP in chloroplasts. This indicates that MP17 harbors hidden plastid targeting sequences. Previous studies showed that posttranslational protein phosphorylation influences PD targeting of MP and virus spread. Analysis of MP17-derived phospho-peptides by mass spectrometry revealed four phosphorylated serine residues (S71, S79, S137, and S140). Site-directed mutagenesis of S71/S79 and S137/S140 showed that the C-terminal serine residues S137/S140 are dispensable for PD targeting. However, exchange of S71/S79 to A71/A79 abolished PD targeting of the mutated MP17 protein. To mimic phosphorylation of S71/S79 both amino acids were substituted by aspartic acid. The resulting D71/D79 variant of MP17 was efficiently targeted to PD. Further deletion analysis showed that PD targeting of MP17 is dependent on the C-terminus, phosphorylation of S71 and/or S79 and a N-terminal domain.
Keywords: MP17; PLRV; phosphorylation; posttranslational modification; intracellular trafficking; plasmodesmata